Profile of Leading Teacher in Implementing Discovery Learning Model to Improve Critical Thinking Skills in Grade V Elementary School Students - Saputri, Rose Andriyani; Riyadi, Riyadi; Matsuri, Matsuri (Eduvest - Journal of Universal Studies, 2025)
Implementation in the era of the 21st-century revolution requires development, knowledge, and skills, with the hope that students are able to think critically and creatively, as well as solve problems and build collaboration together. The purpose of this study is to determine the profile of the driving teacher and the form of development of students' critical thinking skills using the Discovery Learning model in Grade V elementary school students. The research method uses qualitative research, while the data collection technique is conducted through interviews. The results of this study indicate that the driving teacher plays an important role as a facilitator who encourages active, independent, and experience-based learning. They use strategies such as group discussions, trigger questions, and reflection to guide students to find solutions independently. This is in line with the Discovery Learning model, which is designed to improve students' critical thinking skills. The application of the Discovery Learning model shows positive developments in students' critical thinking skills, especially in analysis, evaluation, and problem-solving. Students are more open to different opinions, although self-reflection and creativity need to be improved in some students. In addition, students also show a better understanding of cultural concepts through this approach.